2020
DOI: 10.1097/md.0000000000022543
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic assessments of pediatric supracondylar fractures and mid-term patient-reported outcomes

Abstract: Radiographic parameters are commonly used to determine the need for surgical supracondylar humeral (SCH) fracture reduction and the postoperative quality of reduction. We studied whether such parameters are correlated with mid-term patient-reported outcome (PRO) scores in pediatric patients. We retrospectively reviewed data from 213 patients (104 girls) treated surgically for Gartland type-II (n = 84) or type-III (n = 129) SCH fractures from 2008–2016. Mean (± standard deviation) age at surgery was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Ceiling and floor effects were assessed in 35.3% (n=18/51) of the included studies 8,9,19,21–23,29,31,33,39,40,43,44,49,55,58,59,61. In each of the 18 studies, significant ceiling or floor effects were considered present when ≥15% of the study cohort had reached the maximum or minimum possible score 65.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceiling and floor effects were assessed in 35.3% (n=18/51) of the included studies 8,9,19,21–23,29,31,33,39,40,43,44,49,55,58,59,61. In each of the 18 studies, significant ceiling or floor effects were considered present when ≥15% of the study cohort had reached the maximum or minimum possible score 65.…”
Section: Resultsmentioning
confidence: 99%
“…Ceiling and floor effects were assessed in 35.3% (n = 18/ 51) of the included studies. 8,9,19,[21][22][23]29,31,33,39,40,43,44,49,55,58,59,61 In each of the 18 studies, significant ceiling or floor effects were considered present when ≥ 15% of the study cohort had reached the maximum or minimum possible score. 65 Of note, the 3 most assessed PROMIS domains in terms of ceiling and floor effects were Pain Interference, Mobility, and Upper Extremity (Table 4).…”
Section: Ceiling and Floor Effectsmentioning
confidence: 99%
“…Previous studies have reported a 14% incidence of residual sagittal plane deformity after nonoperative management of type II SCH fractures at short-term follow-up, with equivalent functional outcomes in patients with and without this deformity 37. Radiographic parameters of any kind may not correlate with patient-reported functional outcomes at all 38. Remodeling of coronal plane deformities after fracturing at medium-term follow-up in the distal humerus has been shown to be poor,39 however data is lacking to support or refute remodeling in the sagittal plane.…”
Section: Discussionmentioning
confidence: 97%
“…37 Radiographic parameters of any kind may not correlate with patient-reported functional outcomes at all. 38 Remodeling of coronal plane deformities after fracturing at medium-term follow-up in the distal humerus has been shown to be poor, 39 however data is lacking to support or refute remodeling in the sagittal plane. In our study, some residual deformity was noted at 6-month radiographic follow-up in 62.2% of patients treated nonoperatively, compared with only 44.4% of surgical patients (P = 0.043).…”
Section: Discussionmentioning
confidence: 99%
“…A value between 65° and 82° is considered normal for BA. [ 2 ] Early post-treatment BA and CA were measured right after the cast or splint was removed. A value between 5° and 15° is considered normal for CA and 45° and 57° for LCHA.…”
Section: Methodsmentioning
confidence: 99%